Acinetobacter baumannii in manure and anaerobic digestates of German biogas plants. Issue 10 (24th August 2020) - Pulami, Dipen; Schauss, Thorsten; Eisenberg, Tobias; Wilharm, Gottfried; Blom, Jochen; Goesmann, Alexander; Kämpfer, Peter; Glaeser, Stefanie P
ABSTRACT: Studies considering environmental multidrug-resistant Acinetobacter spp. are scarce. The application of manure on agricultural fields is one source of multidrug-resistant bacteria from livestock into the environment. Here, Acinetobacter spp. were quantified by quantitative polymerase chain reaction in manure applied to biogas plants and in the output of the anaerobic digestion, and Acinetobacter spp. isolated from those samples were comprehensively characterized. The concentration of Acinetobacter 16S ribosomal ribonucleic acid (rRNA) gene copies per g fresh weight was in range of 10 6 –10 8 in manure and decreased (partially significantly) to a still high concentration (10 5 –10 6 ) in digestates. 16S rRNA, gyrB-rpoB and bla OXA51- like gene sequencing identified 17 different Acinetobacter spp., including six A. baumannii strains. Multilocus sequence typing showed no close relation of the six strains with globally relevant clonal complexes; however, they represented five novel sequence types. Comparative genomics and physiological tests gave an explanation how Acinetobacter could survive the anaerobic biogas process and indicated copper resistance and the presence of intrinsic beta-lactamases, efflux-pump and virulence genes. However, the A. baumannii strains lacked acquired resistance against carbapenems, colistin and quinolones. This study provided a detailed characterization of Acinetobacter spp. including A. baumannii released via manure through mesophilic or thermophilic biogas plants into the environment. Abstract : Phylogenetic, phenotypic and genomic characterization of Acinetobacter spp. including A. baumannii cultured from manure and biogas plant digestates of anaerobically digested manure.